Research with Ayahuasca in Psychology: A literature review of its therapeutic potencial - Araújo, Sofia Azevêdo; Tatmatsu, Daniely Ildegardes Brito (Revista de Psicologia, 2020)
The Ayahuasca is a hallucinogenic drink used in religious context and its use is associated with improvements in mental health of users. This study aimed to do a survey of the researches that evaluate the therapeutic potential of Ayahuasca in Psychology. A narrative literature review was performed with the descriptors “Psychology” and “Ayahuasca” indexed on the CAPES portal, on Medline and Scielo platforms. Thirty-four articles were obtained and inclusion criteria were applied - written in Portuguese or English, and having the descriptor “Ayahuasca” in the title - and exclusion - not addressing the therapeutic use of ayahuasca as a research problem. After filtering, we obtained 8 articles published between 2006 and 2018, divided into 10 studies: 7 of basic research and 3 of applied research. It is concluded that the production of studies on the therapeutic efficacy of Ayahuasca and its effects on users' mental health is recent and scarce. It is important that future studies address beyond psychopathological or pharmacological parameters, analising social and cultural issues linked to substance use. It is essential that particularities of the environment in which the substance was taken and of the user's life history are considered and investigated in detail.